THE IMPACT OF RELATIVE DEPRIVATION ON RETURN INTENTIONS AMONG POTENTIAL MIGRANTS AND COMMUTERS1. (17th February 2016) - Huber, Peter; Nowotny, Klaus
ABSTRACT: We empirically analyze the impact of relative deprivation on the intended duration of stay of potential cross‐border commuters and migrants. A theoretical model lends support to the hypothesis that deprivation affects the intended duration of stay of migrants in a U‐shaped fashion, but does not affect potential commuters. Empirical evidence from one of the most densely populated border regions of the EU confirms both these hypotheses. These results are robust over different estimation methods and apply both when measuring deprivation relative to friends and acquaintances as well as relative to the population residing in a region.